In vitro evaluation of fungicides and some plant extracts against rice sheath rot pathogen Sarocladium oryzae (Bangladesh Journal of Scientific Research, 2016)
Sarocladium oryzae (Sawada) W. Gams & D. Hawksworth, the causal agent of sheath rot of rice was isolated from sheath rot infected rice sheaths and grains. Among ten tested fungicides Tall 25 EC completely inhibited radial growth of the fungus even at the lowest concentration 100 ppm. Similarly ethanol leaf extract of ten plants, namely Allium sativum, Artocarpus heterophyllus, Asparagus racemosus, Azadirachta indica, Citrus medica, Datura metel, Mangifera indica, Nerium indicum, Senna alata and Tagetes erecta at 5, 10 and 20% concentrations were screened for their fungicidal activity against the test fungus. All the plant extracts completely inhibited the radial growth of the test fungus at 20% concentration except Asparagus racemosus and C. medica. Ethanol extract of Tagetes erecta and Mangifera indica also completely inhibited the radial growth of the test fungus at 10% concentration.Bangladesh J. Sci. Res. 29(1): 47-54, June-2016